Perceiving truth and value: interdisciplinary discussions on perception as the foundation of ethics - Mühling, Markus; Gilland, David Andrew; Förster-Beuthan, Yvonne (Religion, Theologie und Naturwissenschaft, 2020)
The theme of this volume is the question of value-perception. It is discussed from different philosophical, psychiatric, theological, and anthropological perspectives. The thesis that unites all the papers is the recognition that we live in a relational, dynamic world, in which we primarily perceive, and that to dissolve values from facts is fundamentally misleading, both in theory as in life. The contributions are the outcome of an energetic conference in 2016 where the problems at stake were rigorously discussed. The results are presented here, and they have an explicit order and are strictly related. It opens with basic questions and observations, then critical opinions and objections come into play, after which the outline of a larger theory of value perception is presented, and at the end some concrete examples from material practices are drawn.
Keywords: Aufsatzsammlung; Christliche Ethik; Ethik; Theologische Ethik; Wahrnehmung; Wert